2005
DOI: 10.2741/1667
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species in tumor progression

Abstract: The generation of reactive oxygen radicals in mammalian cells profoundly affects numerous critical cellular functions, and the absence of efficient cellular detoxification mechanisms which remove these radicals can result in several human diseases. Growing evidence suggests that reactive oxygen species (ROS) within cells act as second messengers in intracellular signaling cascades which induce and maintain the oncogenic phenotype of cancer cells. ROS are tumorigenic by virtue of their ability to increase cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
600
0
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 855 publications
(625 citation statements)
references
References 180 publications
13
600
0
12
Order By: Relevance
“…Many studies have shown that ROS-mediated DNA damage can promote oncogenic transformation by increasing mutation rates [33]. In addition to being mutagenic, recent studies have shown that ROS can function as second messengers in signal transduction pathways [34]. These pathways are known to influence various cellular processes such as proliferation, survival, and motility.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that ROS-mediated DNA damage can promote oncogenic transformation by increasing mutation rates [33]. In addition to being mutagenic, recent studies have shown that ROS can function as second messengers in signal transduction pathways [34]. These pathways are known to influence various cellular processes such as proliferation, survival, and motility.…”
Section: Discussionmentioning
confidence: 99%
“…Since FR were accused as causal factors in a large number of diseases, these were sometimes referred as ''Free Radical Diseases''. Some of the important diseases and health issues in this category are cancer [61][62][63][64][65][66][67], cardiovascular diseases [68][69][70][71][72][73], atherosclerosis [74][75][76][77][78][79][80][81], neurological disorders [82][83][84][85][86], renal disorders [87][88][89][90], liver disorders [91][92][93], hypertension [50,94,95], rheumatoid arthritis [96,97], adult respiratory distress syndrome, auto-immune deficiency diseases [98,99], inflammation, degenerative disorders associated with aging [100][101][102][103], diabetes mellitus [104][105]…”
Section: Reactive Oxygen Species and Reactive Nitrogen Species Transimentioning
confidence: 99%
“…Yet, contrary to our hypothesis, which sought to evaluate whether a greater oxidative response correlated with a progressively enlarging tumor, we interestingly observed a greater extent of oxidation stress during the early time intervals than the 6-week time-point. Given the evidence that ROS support tumor growth and progression [15,16], we surmise that at 2 weeks, where oxidative damage is highest, the ROS generated were as a result of a highly proliferative NB cell mass. At 4 and 6 weeks, as the tumor enlarges and develops a necrotic core, subsequent hypoxia ensues, which triggers an elevation of intratumor ROS.…”
Section: Discussionmentioning
confidence: 99%